PENGARUH SOCIAL MEDIA MARKETING DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA SKINCARE GLAD2GLOW DI KOTA JAMBI - Gracella Sophia; Novita Ekasari; Mar Atun Saadah (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of the skincare industry in Indonesia has experienced significant growth along with increasing public awareness of skin care and the influence of social media in marketing activities. One of the emerging local skincare brands is Glad2Glow. This study aims to examine the effect of Social Media Marketing and Price on Purchase Decisions for Glad2Glow skincare products in Jambi City. This research employs a quantitative approach using a survey method by distributing questionnaires to consumers who have used Glad2Glow products. The data analysis technique used is multiple linear regression with the assistance of SPSS software. The results show that partially, Social Media Marketing has a positive and significant effect on Purchase Decisions, with a regression coefficient of 0.601 and a significance value of less than 0.05. In addition, Price also has a positive and significant effect on Purchase Decisions, with a regression coefficient of 0.599 and a significance value of less than 0.05. Simultaneously, Social Media Marketing and Price have a significant effect on Purchase Decisions. These findings indicate that social media marketing strategies and pricing that align with consumer perceptions are important factors in increasing consumer purchase decisions for Glad2Glow skincare products in Jambi City.